Implementasi E-Learning, Learning Management System (LMS), dan Artificial Intelligence dalam Pembelajaran Pendidikan Agama Islam - Sifa Aminatu Jahro; Aliyah Salsabila Putri; Tutus Sandrika; Titik Ayu Kartika (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The advancement of digital technology in the era of the industrial revolution 4.0 has brought significant changes to the educational landscape, including Islamic Religious Education (PAI). The use of e-learning, Learning Management Systems (LMS), and Artificial Intelligence (AI) has emerged as an alternative approach to support learning that is more flexible, interactive, and responsive to students’ needs. This study aims to explore the concepts of e-learning, LMS, and AI within PAI learning, as well as to examine their implementation, benefits, and challenges. This research employs a qualitative approach using a library research method, drawing on various relevant sources such as academic journals, books, and scholarly articles. The results indicate that the integration of these technologies can improve learning effectiveness, foster student engagement, and support more personalized learning experiences. However, challenges such as limited infrastructure and teachers’ readiness in utilizing digital tools are still evident. Therefore, a well-planned and value-oriented strategy is required to ensure that the integration of technology in PAI learning remains aligned with Islamic values while responding to contemporary educational demands.